2015
DOI: 10.5137/1019-5149.jtn.13946-15.2
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of gfap in determining neuron damage in rats with induced head trauma

Abstract: spread neurodegeneration and is still a major worldwide health problem (2,33,44,50,51). TBI causes not only direct mechanical damage to the brain, but it also induces biochemical changes that lead to delayed neural cell loss. These biochemical changes are called secondary injury. The primary █ INTRODUCTION O ne common form of acute brain injury, traumatic brain injury (TBI), is the result of an outside force causing immediate mechanical disruption of brain tissue and delayed pathogenic events that collectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
0
12
0
1
Order By: Relevance
“…Baydas et al [ 68 ] attributed that to HHcy-induced glial cell sensitization. Moreover, previous studies clarified that increased tissue GFAP immunoreactivity was a sensitive indicator of neuronal injury and neuroinflammation [ 69 , 70 ]. However, the VaD + STG group results revealed significant downregulation of GFAP immunoreaction when compared with the VaD group.…”
Section: Discussionmentioning
confidence: 99%
“…Baydas et al [ 68 ] attributed that to HHcy-induced glial cell sensitization. Moreover, previous studies clarified that increased tissue GFAP immunoreactivity was a sensitive indicator of neuronal injury and neuroinflammation [ 69 , 70 ]. However, the VaD + STG group results revealed significant downregulation of GFAP immunoreaction when compared with the VaD group.…”
Section: Discussionmentioning
confidence: 99%
“…* Significantly different from Saline-TBI [Color figure can be viewed at wileyonlinelibrary.com] identifying successful therapeutic approaches to reduce TBI secondary injury (Di Battista et al, 2015). GFAP is an intermediate filament protein specific for astrocytes, and increased GFAP immunoreactivity is a sensitive astrocyte injury biomarker (Cikriklar et al, 2016;Lei et al, 2015;Mondello et al, 2016). GFAP protein is rapidly released into biofluids following cortical injury (Foerch et al, 2012;Y.…”
Section: Discussionmentioning
confidence: 99%
“…GFAP is an astrocyte-specific intermediate filament component of the central nervous system (CNS) and is a common target used for observing the astroglial responses after TBI in vivo experiments (Myer et al, 2006 ; Chen et al, 2012 ). The astrocytes respond to TBI by pronounced changes in cell proliferation and cellular hypertrophy in the lesion site (Myer et al, 2006 ; Babaee et al, 2015 ; Cikriklar et al, 2016 ). In our earlier study using the same diffuse TBI rat model, the upregulation of GFAP has been found at day 1 and remained elevated for at least 1-week post TBI-lesion (Hsieh et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%